Age‐related decrease in CD271+ cells in human skin. Issue 3 (24th August 2015) - Akamatsu, Hirohiko; Hasegawa, Seiji; Yamada, Takaaki; Mizutani, Hiroshi; Nakata, Satoru; Yagami, Akiko; Matsunaga, Kayoko
Abstract: According to recent studies, stem cells are found in various tissues in our bodies. It has been reported that stem cells can reside in the skin tissues, including the epidermis, dermis, hair follicles and subcutaneous tissues. Homeostasis of the skin is maintained because these stem cells collaborate with each other to form new cells. We previously identified the CD271(p75NTR) + cell as a stem cell that was present in the epidermis, dermis and subcutaneous tissue, and further investigated the role of stem cells in wound healing and their association with skin disease. In this study, we investigated the localization of CD271 + cells in human skin (epidermis and dermis) and its age‐related changes in stem cells using CD271 + cells. The study revealed that the number of CD271 + cells in the epidermis and dermis decreased with aging. It is possible that such an age‐related decrease in stem cells causes impaired regenerative ability and is associated with various skin diseases. If the relationship between stem cells and skin aging and diseases can be elucidated by investigations such as this study, it may lead to the development of novel anti‐aging technologies and medical treatments for skin diseases in the future.